Obesity, Insulin Resistance, and Infertility in Women with Polyendocrine Metabolic Ovarian Syndrome: A Retrospective Cohort Study at a Tertiary Referral Medical Center in Qatar - Tahani Ibrahim Alotoum; Husam Qush; Rafea Muftah AlGhanem; Ayman El-Menyar (Healthcare, 2026)
Background: Polyendocrine Metabolic Ovarian Syndrome (PMOS), previously known as Polycystic Ovary Syndrome (PCOS), is one of the most common endocrine disorders affecting women of reproductive age and represents a major cause of infertility worldwide. It is associated with hormonal imbalance, ovulatory dysfunction, and metabolic disturbances, all of which can significantly impair reproductive outcomes and quality of life. We aimed to investigate the metabolic and hormonal markers in infertile women who had PMOS in one of the rapidly developing Middle Eastern countries. Methods: This was a retrospective observational cohort study conducted at the Military Medical Specialist Center in Qatar (2019–2024). Data were extracted from patient medical records, including demographic characteristics, clinical presentation, hormonal profiles, metabolic parameters, and details of fertility treatment. Women aged 18–40 years diagnosed with PMOS according to the Rotterdam criteria were included. Correlation coefficient analysis was performed to assess the associations between PMOS-related factors. Patients were categorized by BMI (normal, overweight, and obese). Results: The mean age of patients was 31.9 ± 5.3 years, and 43.8% of patients were obese. Primary infertility was more frequent than secondary infertility (61.8% vs. 38.2%). Women with secondary infertility were significantly older and had higher body mass index (BMI) (p = 0.001 and p = 0.01, respectively). Insulin resistance was prominent (mean Homeostatic Model Assessment for Insulin Resistance [HOMA-IR] of 4.04) and increased significantly with the increase in BMI (p = 0.01). BMI showed positive correlations with serum levels of glucose, insulin, HOMA-IR, and testosterone. Hormonal parameters were largely comparable between infertility groups, except for lower FSH levels in secondary infertility (p = 0.04). The proportion of PMOS based on the HOMA-IR category was 5.6% (HOMA-IR < 1.0), 23.4% (HOMA-IR 1–1.99), 20.2% (HOMA-IR 2–2.99), and 50.8% (HOMA-IR > 3.00). In PMOS patients, there was a significant association between obesity and HOMA-IR, with each 1-unit increase in HOMA-IR associated with a 14% increase in odds (crude odds ratio 1.14; 95% confidence interval 1.02–1.28, p = 0.02). Also, obesity was associated with low LH/FSH (crude odds ratio, 0.67; 95% CI, 0.45–0.99; p = 0.04). Results: The mean age of patients was 31.9 ± 5.3 years, and 43.8% of patients were obese. Primary infertility was more frequent than secondary infertility (61.8% vs. 38.2%). Insulin resistance was prominent (mean HOMA-IR 4.04) and increased significantly across BMI categories (3.0 in normal-weight vs. 4.8 in obese women, p = 0.01). BMI was positively correlated with HOMA-IR (r = 0.17, p = 0.02) and testosterone levels (r = 0.18, p = 0.01). Secondary infertility became more frequent with increasing BMI (p = 0.02). Each 1-unit increase in HOMA-IR was associated with a 14% increase in the odds of obesity (OR 1.14, 95% CI 1.02–1.28, p = 0.02). Conclusions: Among infertile women with PMOS, obesity and insulin resistance were prominent metabolic characteristics. These findings support routine screening for insulin resistance, particularly in overweight and obese women, together with weight management and individualized fertility treatment based on BMI and metabolic profiles.